Improving single-carbon-nanotube–electrode contacts using molecular electronics - Krittayavathananon, A; Ngamchuea, K; Li, X; Batchelor-McAuley, C; Kätelhön, E; Chaisiwamongkhol, K; Sawangphruk, M; Compton, R (American Chemical Society, 2017)
We report the use of an electroactive species, acetaminophen, to modify the electrical connection between a carbon nanotube (CNT) and an electrode. By applying a potential across two electrodes, some of the CNTs in solution occasionally contact the electrified interface and bridge between two electrodes. By observing a single CNT contact between two microbands of an interdigitated Au electrode in the presence and absence of acetaminophen, the role of the molecular species at the electronic junction is revealed. As compared with the pure CNT, the current magnitude of the acetaminophen-modified CNTs significantly increases with the applied potentials, indicating that the molecule species improves the junction properties probably via redox shuttling.